2022
DOI: 10.5829/ije.2022.35.03c.07
|View full text |Cite
|
Sign up to set email alerts
|

Friction and Wear Performance of Brake Pad and Optimization of Manufacturing Parameters using Grey Relational Analysis

Abstract: Brake pads play very important role in the safety of automobiles as they control the speed of the vehicle. Therefore manufacturing aspects of the brake pads and improvement in their performance were studied in this paper. Experiments are designed based on Taguchi's L9 orthogonal array. Manufacturing pressure, temperature and time are taken into consideration as process variables. Nine sets of experiments were conducted. Each experiment consisted of distinct combination process variables. Thus Brake pads with K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The challenges arise when, for reliable characterization, the lack of any filler/polymer shear slippage, filler debonding and additional voids, microcracks and imperfections at the interface is assumed [8,9]. Such phenomena significantly result in mechanical response exhibited by nano/micro-composites that cannot be easily predicted or engineered through even extensive experimental observations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The challenges arise when, for reliable characterization, the lack of any filler/polymer shear slippage, filler debonding and additional voids, microcracks and imperfections at the interface is assumed [8,9]. Such phenomena significantly result in mechanical response exhibited by nano/micro-composites that cannot be easily predicted or engineered through even extensive experimental observations [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial interactions may be governed by the thermodynamic compatibility and the chemical affinity of the reinforcement and polymer, the dispersion/distribution quality of fillers, crystallization characteristics of the matrix, and the processing technique used. The latter is reported to govern overall performance of thermosetting parts filled with micro/nano-reinforcements [4,5]. It has been reported that the higher the strength of the interfacial interactions, the greater the level of fillers dispersion [6].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve the required wire-ED machining performance, various optimization techniques [11][12][13][14][15][16][17][18] such as, Grey Relational Analysis (GRA), Principal Component Analysis, Taguchi method, Response Surface Methodology (RSM), etc., have been employed. Design of experiments approach has also been utilized to analyze the effects of process parameters on the machining characteristics of Titanium alloys [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Design of experiments approach has also been utilized to analyze the effects of process parameters on the machining characteristics of Titanium alloys [19,20]. Among these techniques, GRA is a normalization based statistical analysis technique, and is one of the most popular and effective techniques for multi-objective or multi-performance optimization of the process parameters, which can carry out minimization of certain parameters while simultaneously maximizing the others [11,[17][18]. GRA is especially suitable when the system under consideration consists of a complex interplay of various factors and their overall effect in combination needs to be quantitatively analyzed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation